BIDADARI DAN SI PENGGODA REPRESENTASI TOKOH-TOKOH PEREMPUAN DALAM NOVEL STUDENT HIDJO - Novi Diah Haryanti (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2017)
Abstract: This paper examines the representation of women characters in the novel “Student Hidjo” (SH) and how the world of movement affects Mas Marco Kartodikromo in creating his female characters. In his depiction of the female character, Marco uses the European (Dutch) and the Javanese, or in post colonial terms the West (Dutch) and East binary opposition. By re-reading this literary work, it appears that Marco portrayed the native female character as angel while the Dutch female character as vampish. Marco also shows that European woman is not always perfect, independent, and superior, while the native woman is not always weak, ignorant, left behind, dan only thinking about the affairs of love (household). Abstrak: Tulisan ini akan mengulas bagaimana representasi tokoh-tokoh perempuan dalam novel Student Hidjo (SH) dan bagaimana dunia pergerakan mempengaruhi Mas Marco Kartodikromo dalam menciptakan tokoh perempuan. Dalam menggambarkan tokohnya, Marco menggunakan oposisi binner Eropa (Belanda) dan Jawa atau dalam istilah pascakolonial Barat/Timur. Melalui hasil re-reading terhadap karya tersebut tampak bahwa Marco mencitrakan perempuan pribumi sebagai bidadari sedangkan perempuan Belanda sebagai si penggoda. Lewat Student Hidjo Marco memperlihat bahwa perempuan Eropa tak selamanya sempurna, mandiri, dan superior sedangkan perempuan pribumi tak selalu lemah, bodoh, tertinggal, dan hanya memikirkan urusan cinta (rumah tangga). Permalink/DOI: http://dx.doi.org/10.15408/dialektika.v4i1.7002